Physiotherapists' experiences of interactions with inter-professional team members in the adult intensive care unit (ICU) setting - Ntinga, Mahitsonge Nomusa (My University, 2017)
Introduction: Inter-professional team collaboration allows for enhanced patient safety, better use of resources by avoiding duplication of treatment, and improved standards of patient care as the time and skills of the professionals is efficiently utilised. In environments where the patients are highly dependent on the caregiver such as the intensive care unit (ICU), patient safety is of utmost priority and ensuring this safety requires collaboration of all professionals attending to the patient. The willingness to follow evidence based practice (EBP) and inter-professional team collaborative protocols become tools to ensure the ICU patients’ survival. Physiotherapists, through respiratory therapy, help reduce rates of ventilator associated pneumonia, time spent on mechanical ventilation and early mobilisation exercises aid in preventing ICU acquired weakness, which is a consequence of prolonged bed rest, and therefore reduces length of stay (LOS) in ICU and in hospital. There is evidence that using inter-professional team inclusive weaning protocols results in a shorter, more effective weaning process, which is most beneficial to patient outcomes and implementing interactive learning/education inclusive of all members. This allows for auditing and feedback and continuous professional development of the team. There is currently no research done in South Africa that explores, from the physiotherapist’s perspective, the collaboration, interactions and communication between physiotherapists and the interprofessional team members in the ICU setting. This study was conducted to establish physiotherapists’ experiences of interactions with the inter-professional team members in an adult ICU setting.
Keywords: Intensive Care Units; Evidence-Based Practice